The Effect of Total Asset Turnover and Leverage on Profitability Case Study on Property and Real Estate Service Industry Companies Listed on the Indonesia Stock Exchange (IDX) - Reka Yulinda (LPPM Universitas Lembah Dempo, 2022)
ABSTRACT The Effect of Total Asset Turnover and Leverage on Profitability Case Study on Property and Real Estate Service Industry Companies Listed on the Indonesia Stock Exchange (IDX) REKA YULINDA NPM : 171000461201044 UNIVERSITAS MAHAPUTRA MUHAMMAD YAMIN SOLOK Companies with good performance will be able to achieve the goals to be achieved by the company, namely maximizing company value. This goal can be achieved by increasing the company's profitability. The purpose of this study was to determine the effect of Total Asset Turnover and Leverage on Profitability. This research was conducted at the Property and Real Estate Service Industry companies on the Indonesia Stock Exchange with a sample of 10 companies obtained through purposive sampling method. The results of the study using multiple linear analysis, namely Y = 0.002 + 0.321X1 - 0.009X2 with the explanation that Total Asset Turnover has a positive and significant effect on profitability, while Leverage (DER) has a negative and insignificant effect on profitability. Keywords: Total Asset Turnover, Leverage (DER) and Profitability (ROA).